Between Love and Marriage: Dilemma of Gay's Love (A Qualitative Study of Phenomenology in Gay People) - Gumi Langerya Rizal (International Conference of Mental Health, Neuroscience, and Cyber-psychology)
Being a life partner and having a family is one of the tasks of personal development in early adulthood, as well as a homosexual person or a gay person. Differences in sexual orientation and rejection in relation to the environment, family and religion, however, make the desire to get marry being a conflict in a gay person. In this study, the author highlights the phenomenon of the inner conflict between love and marriage that occurs in a gay person. The author reveals phenomenology to express the experience and psychological dynamics of a gay person who wishes to change and marry. The results showed that a person with homosexual has a great desire to change and marry. However, this desire is not a wish or a hope that is easy for a gay person to realize. Many experiences have been shared, views on his life, fears, conflicts and hopes that exist in him, which also encourage and complicate his desire to marry.